Corrosion for Everybody - Groysman, Alec.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
People seldom enjoy corrosion. They usually perceive it as a nasty phenomenon with which they must cope. Yet many people, far from the corrosion field, come across it because of their professional duty. Lawyers, historians, doctors, architects, philosophers, artists, and archeologists, to name a few, may want or need to understand the principles of corrosion. This volume explains this important topic in a lucid, interesting, and popular form to everybody: to students and young engineers who are only beginning their studies, to scientists and engineers who have dealt with corrosion for many years, and to non-specialists involved in corrosion problems. The book uses a fresh writing style, with some new explanations relating to thermodynamics of oxidation of iron and mild steels in water, reversible and irreversible potential, solubility of oxygen in water and aqueous solutions of electrolytes, corrosion of metals in fuels, corrosion of storage tanks for fuels and their corrosion control, corrosion monitoring in practice, humanitarian aspects of corrosion science and technology (history of the evolution of knowledge about corrosion, relationships between corrosion and philosophy, corrosion and art). Many practical examples of various corrosion phenomena are given.
Corrosion Mechanism and Corrosion Factors -- Corrosion Phenomena -- Corrosion in Natural and Industrial Environments -- Corrosion Control Measures -- Corrosion Monitoring -- Humanitarian Aspects of Corrosion Science and Technology.
Keywords: Materials; Chemistry, inorganic; Material Science; Tribology, Corrosion and Coatings; Materials Science, general; Metallic Materials